1998
DOI: 10.1016/s0006-3495(98)77695-7
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of the Corneal and Limbal Fibrils in the Human Eye

Abstract: The precise orientation of the collagen fibrils in human cornea and sclera and the method by which these two areas fuse together at the limbus have never been determined, despite the importance of this information. From a consideration of the mechanics of the system, fibril orientation in the tissue has the potential to affect the curvature of the cornea so, by inference, refractive problems such as astigmatism involving an incorrect curvature of the cornea may be related to fibril orientation. The high intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(74 citation statements)
references
References 12 publications
5
64
0
5
Order By: Relevance
“…7, SHG microscopy showed that the collagen fiber of sclera was parallel to the limbus. This is consistent with previous reports about the scleral structure [46,51,52]. In contrast, the collagen fiber of the posterior sclera shown in Fig.…”
Section: Discussionsupporting
confidence: 94%
“…7, SHG microscopy showed that the collagen fiber of sclera was parallel to the limbus. This is consistent with previous reports about the scleral structure [46,51,52]. In contrast, the collagen fiber of the posterior sclera shown in Fig.…”
Section: Discussionsupporting
confidence: 94%
“…6(e) and 6(g), which showed high entropy but low local retardation. Since this region corresponds to the corneoscleral limbus, where the corneal and scleral laminar tissues change transitionally with fibrovascular ridges [60,61], the anisotropic fibrous structure might have anisotropic optic axes in the kernel window and have resulted in the high entropy. It is known that such anisotropic fibrous structure can be found at various biological tissues [62][63][64].…”
Section: Estimation Of H Noise At a Single Depthmentioning
confidence: 99%
“…The concentration of the collagen fibril orientations towards the circumferential direction at the limbus predicted by the remodeling algorithm can be interpreted as the development of a fibrillar annulus. From synchrotron X-ray diffraction data, the existence of a circumcorneal annulus of collagen fibrils at the limbus is well known (Newton and Meek 1998). The density of corneal fibril orientations of both families ρ fam1 (ϕ) + ρ fam2 (ϕ) predicted by the remodeling algorithm at the biological equilibrium (t/t * = 20) is compared in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Meek et al (1989) reported, using X-ray fibril diffraction, that the network of collagen fibrils in the central region of human corneas is characterized by two preferred directions, superior-inferior and nasal-temporal. Toward the limbus, there was only one preferred direction tangential to the limbus, where a circumcorneal annulus of collagen fibrils has been observed (Newton and Meek 1998;Aghamohammadzadeh et al 2004).…”
Section: Introductionmentioning
confidence: 99%